Acute Management of Cocaine-Associated Methaemoglobinaemia - Immo Weichert (Case Reports in Medicine)
Methaemoglobinaemia is a potentially life-threatening complication of problem drug use. This is a case report of a 29-year-old man who presented himself cyanosed after a cocaine binge. It highlights the diagnosis and management of this condition from an acute medical perspective.